PENGEMBANGAN BAHAN AJAR MATERI SEGIEMPAT DAN SEGITIGA KELAS VII SMP/MTs BERBASIS PERMAINAN TRADISIONAL MELAYU RIAU - Vevi Anggia; Yenita Roza; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The background of this research is the lack of student’s textbook that introduced regional resources to students in accordance with the demands of 2013 curriculum.This research purposed is to develop student’s textbook in the form of books that introduce regional resources to students by introducing traditional games of Riau malay. This research is a research and development (R&D) that using 4-D model which consists of 4 stages define, design, develop and dissemination, but in this research is only carried out until the development stage . The instrument used in this research is a validation sheet to assess the validity of textbook. Based on the results of validation data analysis the average rating for the textbook is 3.57 with a very valid category. Based on the results of data analysis and discussion it can be concluded that mathematic student’s textbook developed that using the traditional games of Riau malay on rectangular and triangular has fulfilled valid criteria.Keywords: Mathematics Learning, Mathematic Student’s Textbook, Riau Malay Traditional Games, 4-D Development Model